2016
DOI: 10.1515/msp-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Study of high-strength and high-conductivity Cu–Sn–Fe alloys

Abstract: Cu-Sn-Fe alloys with different compositions were developed by casting, normalizing treatment, cold roll and subsequent annealing treatment. The results showed that the tensile strength and resistivity of the Cu-xSn-xFe alloys (where x represents wt.%) improved with increasing the content of Sn and Fe. Compared with the as-cast alloys, the resistivity and tensile strength of the Cu-xSn-xFe alloys after normalizing and cold rolling treatment increased. In addition, the resistivity and mechanical properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Currently, in order to improve the properties of materials, not pure copper is introduced into the iron base, but alloys based on it, such as bronze powder. The combination of Fe, Cu and Sn has been shown in the creation of composite alloys of the Fe-Cu-Sn system [14][15][16][17]. Iron, copper, and tin composites are used in various tribological applications due to their high hardness, high strength, and moderate wear resistance [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, in order to improve the properties of materials, not pure copper is introduced into the iron base, but alloys based on it, such as bronze powder. The combination of Fe, Cu and Sn has been shown in the creation of composite alloys of the Fe-Cu-Sn system [14][15][16][17]. Iron, copper, and tin composites are used in various tribological applications due to their high hardness, high strength, and moderate wear resistance [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of Fe, Cu and Sn has been shown in the creation of composite alloys of the Fe-Cu-Sn system [14][15][16][17]. Iron, copper, and tin composites are used in various tribological applications due to their high hardness, high strength, and moderate wear resistance [16,17]. It was noted in [17] that the ultimate strength and resistivity of Cu-Sn-Fe alloys increase with increasing Sn and Fe content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the low preparation cost and abundant raw materials, Cu-Fe alloy has been widely concerned and extensively explored [9][10][11][12][13][14]. J. T. Zhang et al [15] found that the solidification microstructure of the high strength and high conductivity Cu-Fe-Sn alloy prepared by use of copper mould rapid cooling method can be refined. After cold deformation to a certain extent and annealing at a certain temperature, the comprehensive properties of the alloy can be improved.…”
Section: Introductionmentioning
confidence: 99%